Comparison of Body Mass Index (BMI), before and post COVID-19, across different age groups in the population of Northeast Portugal - Bragada, José A. (2023)
Over the last few decades, there has been a significant increase in obesity levels, particularly developed countries. This rise primarily reflects changes in dietary patterns, the rise of sedentary lifestyles, and socioeconomic factors. The Body Mass Index (BMI) has been a widely used parameter with the intention of evaluating body fat at any age (1,2). Although it's not the most rigorous method (3), it has the advantage of being easy to calculate and having many records available. In Portugal, there has also been an increase in the prevalence of obesity and overweight in recent years (4). The pandemic period (COVID-19), which lasted approximately 2 years (2020 and 2021), led to lifestyle changes for many people, often resulting in a notable decrease in physical activity. How has this period affected the BMI of these specific population?